PENGARUH KREDIBILITAS AKUN INSTAGRAM @ANAKMAGANG.ID TERHADAP PEMENUHAN KEBUTUHAN INFORMASI MAGANG (Survei pada followers akun instagram @anakmagang.id) - Vera Nurul Fadilah (2024)
Rapid technological advances, making social media today become one of the sources of information. Based on Indonesibaik.id data 97% of social media users are dominated by individuals with Diploma / S1 backgrounds. KIC (Katadata Insight Center) together with KOMINFO explained that 73% of people use social media to find information and 22.4% of respondents consider that social media can be trusted as a source of information. The purpose of this study was to determine how much influence the credibility of the @anakmagang.id Instagram account has on meeting the information needs of internships. The theory used is the theory of media credibility. This study used a quantitative approach. The sample of this study is Instagram followers @anakmagang.id, active S1 students in Indonesia, and have registered for an internship (at least once) based on information obtained from the @anakmagang.id Instagram account. This research method is a survey by distributing an online questionnaire to 100 respondents. The results of the hypothesis test stated Ho was rejected and Ha was accepted. That is, there is an influence of Instagram Account Credibility @anakmagang.id (variable X) on the fulfillment of internship information needs (variable Y). It was obtained from the t count > t table, which is 9,449 > 1,660. The results of the coefficient of determination test showed that 47.7% of Instagram account credibility affected the fulfillment of information needs and 52.3% was influenced by other factors outside the study. This research supports the theory of media credibility as evidenced by the results of respondents' positional responses that the @anakmagang.id Instagram account as an information medium can meet the information needs of interns for their followers.